Sorting Machine of Ecopaving Materials Based on Digital Image Processing - Agung Samudra, Bayu; Sukardi (Journal of Industrial Automation and Electrical Engineering, 2024)
This final project focuses on the design and development of a prototype waste sorting machine with the goal of aiding the production of ecopaving by sorting plastic waste through digital image processing techniques. The main objective of this research is to address the environmental issues caused by household plastic waste, which has become a significant global challenge, especially in Indonesia. The proposed system uses a conveyor belt mechanism and integrates digital image processing programmed with Python, utilizing a Convolutional Neural Network (CNN) model for image classification. The prototype sorts waste into three categories: plastic, glass, and metal, using a webcam for detection and a servo motor to push the sorted materials. The automation of this system aims to improve efficiency and accuracy in the sorting process, reduce reliance on manual labor, and minimize processing time. This approach not only contributes to waste management but also promotes the recycling of plastic waste into valuable products such as ecopaving, in line with the 3R principle (Reduce, Reuse, Recycle). This final project is expected to provide an effective and efficient solution in reducing waste so that it can be more useful rather than just environmental waste